Objectivity, Control and Adaptability in Corporate Governance - Arnoud W.A. Boot; Jonathan R. Macey (Tinbergen Institute, 1998)
Countries appear to differ considerably in the basic orientations oftheir corporate governance structures. We postulatethe trade-off between objectivity and proximity as fundamental tothe corporate governance debate. We stress thevalue of objectivity that comes with distance (e.g. the marketoriented U.S. system), and the value of better informationthat comes with proximity (e.g. the more intrusive ContinentalEuropean model).A superior corporate governance arrangement must balance thebenefits of proximity and objectivity. In this context,we also discuss the ways in which investors have contracted aroundthe flaws in their own corporate governancesystems, pointing at the adaptability of different arrangements.
Keywords: 330; Corporate Governance; Theorie